2017
DOI: 10.1530/erc-16-0464
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of metastatic pancreatic neuroendocrine tumors: relevance of ENETS 2016 guidelines

Abstract: The choice of first-line treatment for metastatic pancreatic neuroendocrine tumors (mP-NET) is mainly based on prognostic factors. ENETS-2016 guidelines stratified treatment according to 3 groups: Group 1, patients in whom all lesions could be removed; Group 2, patients with Ki67 <10%, low tumor burden, no symptoms and stable disease, for whom a watch-and-wait strategy or somatostatin analogs are proposed; Group 3, symptomatic patients or with Ki67 >10% or significant tumor burden or progressive disease, for w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…Regarding prognostic factors, similar to that found for digestive NETs, poor ECOG PS, higher tumor grade (atypical subtype according to the WHO classification), high tumor burden (high CgA levels which is reported to be correlated with tumor burden), and absence of uptake on SRS were significantly associated with poor survival. 29,31,32 WHO classification is currently based on primary tumor analysis and its relevance at the metastatic stage has yet to be established; herein, however, we found that WHO classification remained a strong prognostic factor at the metastatic stage. In contrast with the digestive WHO classification, Ki67 is not required in the lung WHO classification.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Regarding prognostic factors, similar to that found for digestive NETs, poor ECOG PS, higher tumor grade (atypical subtype according to the WHO classification), high tumor burden (high CgA levels which is reported to be correlated with tumor burden), and absence of uptake on SRS were significantly associated with poor survival. 29,31,32 WHO classification is currently based on primary tumor analysis and its relevance at the metastatic stage has yet to be established; herein, however, we found that WHO classification remained a strong prognostic factor at the metastatic stage. In contrast with the digestive WHO classification, Ki67 is not required in the lung WHO classification.…”
Section: Discussionmentioning
confidence: 54%
“…3 Regarding the modality of tumor spread, both herein and in the LUNA study, the main metastatic site was the liver, as has been reported for digestive NETs; however, the frequency of bone and lung sites was much higher in MLC patients. 5,28 Uptake on FDG-PET was more frequent herein than in digestive NETs, 3,29 yet bias cannot be excluded because only half the patients underwent this examination which may be prescribed for more aggressive disease (this was not reported in the LUNA study 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…2). A diagnosis of pancreatic neuroendocrine tumour was established, with consequently indication to surgery [6]. A distal splenopancreatectomy and cholecystectomy with laparoscopic approach was performed: intraoperatively, we confirmed the presence of a large solid mass, hyper-vascularized, strictly adherent to mesocolon.…”
Section: Case Presentationmentioning
confidence: 84%
“…Regimens included dacarbazine, streptozotocin, oxaliplatin, cisplatin–etoposide, and everolimus. Radiofrequency ablation and chemoembolization have also been used in pediatric pNETs . Furthermore, neuroendocrine tumors have been found to respond to octreotide and peptide receptor radionuclide therapy due to their high expression of somatostatin receptors .…”
Section: Discussionmentioning
confidence: 99%